Production of Disinfectant by Utilizing Eco-enzyme from Fruit Peels Waste - Rusdianasari; Adi Syakdani; Muhammad Zaman; Febby Fitria Sari; Nabila Putri Nasyta; Rizka Amalia (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Organic waste is waste that contains carbon compounds that come from living things, such as fruit and vegetable waste. However, the community is still not able to manage it optimally, even though organic and non-organic waste can still be processed into useful products. This effective way can be realized through the manufacture of eco-enzymes that can be applied at the household level. Eco-enzyme is a liquid extract produced from the fermentation of vegetable and fruit residues with brown sugar as a substrate. The eco-enzyme has a strong sweet and sour fermented aroma due to the peels of oranges, pineapples, and papayas. This environmentally friendly enzyme can be produced using fruit peel, brown sugar, and water. Eco-enzyme solution when mixed with water, will react and can be used as a liquid disinfectant. Disinfectants commonly used are generally derived from synthetic chemicals in the form of artificial chemicals. One of the natural ingredients that can be used as a disinfectant is eco-enzyme liquid. This study aims to make a disinfectant using an environmentally friendly enzyme liquid, namely eco-enzyme. The method used in this research is a mixed method of fermentation of orange peel waste, pineapple and papaya, brown sugar, and water with a ratio of 3:1:10. Analysis for eco-enzyme pH, and Phytochemicals, while for disinfectants include pH, total phenol content with UV-Vis Spectrophotometer, hard water emulsion stability, and antibacterial test. All samples of the disinfectant product met the requirements of SNI 06 – 1842 of 1995, besides that, the best disinfectant product was found in a ratio of 1:10 which could reduce bacterial growth.